Factors encouraging participation in social activities after hospital discharge in people with severe mental illness who received occupational therapy - Nagashima, Izumi; Hayasaka, Tomonari; Teruya, Koji; Hoshino, Miku; Murao, Masami; Matumoto, Yasuyuki; Maruki, Taku; Katagiri, Takeshi; Imamura, Yayoi; Kurihara, Mariko; Oe, Yuki; Tsuboi, Takashi; et al. (Frontiers in Psychiatry, 2024)
Introduction: Occupational therapy (OT), a vital part of psychiatric rehabilitation, encourages participation in social activities, which is critical for the recovery of people with severe mental illnesses (SMI). However, the effects of OT on the subsequent social activities of patients with SMI have not been fully clarified. We aimed to identify the factors that encourage post-discharge social activity participation among patients with SMI who received OT. Method: Patients who underwent OT at the Kyorin University Hospital between April 2016 and March 2020 were retrospectively examined for baseline data during hospitalization and social activity status 1 year after discharge. Occupational support, group adaptation, artistic activities, and exercise programs were considered. Activities requiring social interaction were defined as social activities, including employment, schooling, sheltered work, and volunteer work. Multiple logistic regression analyses using demographic and medical data, prehospitalization social activity status, and OT participation rates as independent variables were used to examine the factors encouraging social activity participation after discharge. Decision tree analysis was conducted to identify patients who specifically needed to increase OT participation. Results: Of 524 eligible patients, 247 were included in the study. The number of patients who were socially active at admission and after discharge was 116 and 188, respectively. Multiple logistic regression analyses revealed that the following factors were likely to encourage social activity participation after discharge: higher rates of OT participation to facilitate group adaptation (OR = 1.015, 95% CI 1.003-1.027), being socially active at admission (OR = 4.557, 95% CI 2.155-9.637), and no marital history (OR = 0.293, 95% CI 0.130-0.661). Decision tree analysis showed that for patients who were socially inactive at admission and had a history of marriage, increasing OT participation to 52.6% or higher may ensure social activity participation after discharge. Conclusions: This study identified patients whose social participation after discharge could be boosted by OT that facilitates group adaptation. Our findings would facilitate the development of individualized add-on rehabilitation based on the effects of real-world OT practices.